Interobserver variability of 3.0-tesla and 1.5-tesla magnetic resonance imaging/computed tomography fusion image–based post-implant dosimetry of prostate brachytherapy. (13th May 2019) - Watanabe, Kenta; Katayama, Norihisa; Katsui, Kuniaki; Matsushita, Toshi; Takamoto, Atsushi; Ihara, Hiroki; Nasu, Yasutomo; Takemoto, Mitsuhiro; Kuroda, Masahiro; Kanazawa, Susumu
Abstract: This study aimed to compare the interobserver variabilities in magnetic resonance imaging (MRI)/computed tomography (CT) fusion image–based post-implant dosimetry of permanent prostate brachytherapy (PPB) between 1.5-T and 3.0-T MRI. The study included 60 patients. Of these patients, 30 underwent 1.5-T MRI and CT 30 days after seed implantation (1.5-T group), and 30 underwent 3.0-T MRI and CT 30 days after seed implantation (3.0-T group). All patients received PPB alone. Two radiation oncologists performed MRI/CT fusion image–based post-implant dosimetry, and the interobserver variabilities of dose–volume histogram (DVH) parameters [dose (Gy) received by 90% of the prostate volume (prostate D90)], percentage of the prostate volume receiving at least the full prescribed dose (prostate V100), percentage of the prostate volume receiving at least 150% of the prescribed dose (prostate V150), dose (Gy) received by 5% of the urethral volume (urethral D5) and the urethral volume receiving at least 150% of the prescribed dose (urethral V150)] were retrospectively estimated using the paired Student's t test and Pearson's correlation coefficient. The Pearson's correlation coefficients of all DVH parameters were higher in the 3.0-T group than in the 1.5-T group (1.5-T vs 3.0-T: prostate D90, 0.65 vs 0.93; prostate V100, 0.62 vs 0.82; prostate V150, 0.97 vs 0.98; urethral D5, 0.92 vs 0.93; and urethral V150, 0.88 vs 0.93). In the paired Student's t test, no significant differences were observed in any of the DVH parame t ers between the two radiation oncologists in the 3.0-T group (0.068 ≤ P ≤ 0.842); however, significant differences were observed in prostate D90 ( P = 0.004), prostate V100 ( P = 0.011) and prostate V150 ( P = 0.002) between the oncologists in the 1.5-T group. The interobserver variability of DVH parameters in the MRI/CT fusion image–based post-implant dosimetry analysis of brachytherapy was lower with 3.0-T MRI than with 1.5-T MRI.